Critical points of change in the blackberry productive chain (Rubus glaucus Benth) in the municipality of Pamplona, Colombia (2019)
A diagnosis of the blackberry (Rubus glaucus Benth) production chain was made in the municipality of Pamplona, Colombia, using a mixed approach. In quantitative terms, the following variables were studied: research, good agricultural practices and post-harvest management. Qualitatively, the weaknesses of the production chain and the improvements required were studied, based on interviews with experts. As a result, it was obtained that the blackberry productive chain presents strengths, such as: sufficiency of spaces for sowing, adaptation and yield of the fruit to the soils, considerations of the medicinal and nutritional value of the product, among others. However, there are critical points regarding to the genetic improvement of crops, lack of routines for water analysis and adequate disinfection, along with bad practices in the technical management of the crop. It is also evident that producers do not use administrative tools or keep accounting records to guide decision-making.